Filmes domésticos : uma abordagem a partir do acervo da Cinemateca Brasileira - Foster, Lila Silva (2010)
Cinemateca Brasileira, the largest film archive in Brazil, for years has stored, catalogued and conserved a large number of Brazilian films that have survived to the present day. But in order for a film to be thoroughly preserved it needs to be known by both the general public and specialized audiences. Some collections manage to be fully preserved while others remain stored without the adequate circulation: this is the case of the home movies collection. The aim of the current research is the valorization of this collection through its physical description and the investigation about its content. Throughout this process, the cataloguing procedures currently in practice at the archive and the specificities of the collection of home movies regarding its informational status will be described. From this investigation specific work methods and forms of analysis will be proposed. In a broader perspective, historical background and conceptual discussions about the formation of the amateur field, the use of cinema in the domestic realm, the production of images in the private domain and the amateur cinema columns of the magazine Cinearte will add to the cataloguing procedures of Cinemateca Brasileira.